Effect of Graphene addition on the mechanical and tribological behavior of nanostructured AA2124 /Graphene self-lubricating metal matrix composite - EL Ghazaly, Ahmed Hazem (AUC Knowledge Fountain, 2017)
In the current research, the mechanical and tribological behavior, and structural evolution of AA2124-3 and 5-wt.% graphene (G) composites prepared by a combination of ball milling and hot extrusion were investigated. Mixing followed by energy ball milling of the powders was conducted under argon atmosphere. Hot extrusion of the green compacts was carried out at 0.46 and 0.68 of the alloy melting temperature. Properties such as macro and micro-hardness, nanohardness, tensile and lattice strain were characterized. Wear rates, coefficient of friction (COF) were characterized using dry pin-on-disc test under loads of 50, 100N and 150N. Nanoscratch testing were employed to investigate the self-lubricating tribological behavior. X-ray diffraction, optical and scanning electron microscopy were used to determine the influence of the G-content on the crystallite size variation and the lattice strain for the ball milled powders compared to the hot extruded rods. Density measurements and optical microscopy (OM) were employed to investigate the consolidation degree and porosity variation as a function of increasing G- of the G and Al-matrices for the variable conditions. Bulk texture variation was analyzed to evaluate the influence of the extrusion temperature. AA 2124-3 wt.% G composites displayed the highest tensile properties, highest hardness and lowest wear rates and COF, as well as lowest scratch width and depth compared to the 5 wt.%G and the plain alloy. The uniform distribution of the G-particles within the Al-matrices for the 3wt.% containing composites hindered grain coarsening by the induced lattice strain compared to that of 5 wt% G ones. Moreover, addition of 3 wt.% G smeared thin uniform tribofilm on the surfaces of the worn composite rods. The formed layer reduced friction and wear. Increasing the G content up to 5 wt.% resulted in segregation and clustering of the G-particles within the Al-matrices, which caused microplouging and sever plastic deformation wear mechanism and excessive delamination. IV Lower consolidation temperatures of 300oC produced composites with lower wear rates due to the excessive strain hardening effect. Extrusion at 300oC produced a continuous G-encapsulating layer around the Al-matrix compared to an interrupted G-layer for the 450oC extrusions. The G-layer morphology influenced the dominating mechanism of the composite during deformation. Texture analysis of the AA2124-3 wt.%G extruded at low and high temperatures proved that both the Cu-and Shear are the dominating texture components, while increased texture intensities from 1.2-to-1.76 occurred with increasing the extrusion temperature.